The Dynamics of Cow Farmer Group towards the Development of Feed Canning Technology - Bakhtiar, Ary; Mahmud, Ali; Agustina, Yohana; Rizki Novanda, Ridha; Oryza Anantha Helian Thus, Orca; Fibriyanti, Dian; Maisaroh, Samae (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 1 (2022): Vol.16, No.1, 2022DO - 10.24843/SOCA.2022.v16.i01.p09, 2022)
Malang Raya area as a contributor of livestock product which is dairy cow's milk, do not escape from problem of increasing the number of farmers but not accompanied by an increase in milk production. This can be influenced by two kinds of factors such as genetic factors and external environmental factors such as feed. The above problems certainly underpinned renewal, to improve feed quality such as feed canning techniques, where the dynamics level of a group influenced the level of adaptation and distribution of these innovations. This research aimed to determine the dynamics of dairy farmers in Malang Raya Regency and the influence of group dynamics on the development of forage canning technology. The research location was determined purposively, where the location chosen would represent Malang Raya Regency with the majority of the people working as dairy farmers. The number of respondents in this research was 62 people who were determined by the purposive random sampling method. The research method used was descriptive analysis and case studies. Methods of collecting data used interviews, questionnaires, observations and documentation, to obtain primary and secondary data. The results showed that the dynamics of the majority group were in the moderate category, while group pressure was the only aspect that occupied the high category, in which 74.6%. Group pressure had a big influence on the motivation in performing activities to realize group goals, and the pressure was expected can change behavior, attitudes, ideas and mutual trust between members